Analysis of Intent and Reason for Oncologic Therapy Administration in Cancer Patients Admitted to the Intensive Care Unit. (October 2022) - Shaz, David; Pastores, Stephen M.; Dayal, Lokesh; Berkowitz, Justin; Kostelecky, Natalie; Tan, Kay See; Halpern, Neil
Purpose: To investigate the intent of, and reason for, administration of oncologic therapies in the intensive care unit (ICU). Methods: Single center, retrospective, cohort study of patients with cancer who received oncologic therapies at a tertiary cancer center ICU between April 1, 2019 and March 31, 2020. Oncologic therapies included traditional cytotoxic chemotherapy, targeted therapy, immunotherapy, hormonal or biologic therapy directed at a malignancy and were characterized as initiation (initial administration) or continuation (part of an ongoing regimen). Results: 84 unique patients (6.8% of total ICU admissions) received oncologic therapies in the ICU; 43 (51%) had hematologic malignancies and 41 (49%) had solid tumors. The intent of oncologic therapy was palliative in 63% and curative in 27%. Twenty-two (26%) patients received initiation and 62 (74%) received continuation oncologic therapies. The intent of oncologic therapy was significantly different by regimen type (initiation vs. continuation, p = <0.0001). Initiation therapy was more commonly prescribed with curative intent and continuation therapy was more commonly administered with palliative intent (p = <0.0001). Oncologic therapies were given in the ICU mainly for an oncologic emergency (56%) and because the patients happened to be in the ICU for a non-oncologic critical illness when their oncologic therapy was due (34.5%). Conclusion: Our study provides intensivists with a better understanding of the context and intent of oncologic therapies and why these therapies are administered in the ICU.